2005
DOI: 10.1093/hmg/ddi375
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mutations in mouse Chd7 provide models for CHARGE syndrome

Abstract: Mouse ENU mutagenesis programmes have yielded a series of independent mutations on proximal chromosome 4 leading to dominant head-bobbing and circling behaviour due to truncations of the lateral semicircular canal of the inner ear. Here, we report the identification of mutations in the Chd7 gene in nine of these mutant alleles including six nonsense and three splice site mutations. The human CHD7 gene is known to be involved in CHARGE syndrome, which also shows inner ear malformations and a variety of other fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
227
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(253 citation statements)
references
References 61 publications
21
227
3
2
Order By: Relevance
“…Four benign variants (p.Ser103Thr, p.Met340Val, p.Gly522Val, and p.Phe2750Leu) were found in more than 15 index persons. Two of these variants (p.Ser103Thr and p.Gly522Val) were found in homozygous states and are, therefore, surely benign (mice with homozygous CHD7 mutations die in early embryogenesis [Bosman et al, 2005] and homozygous CHD7 mutations have never been found in a patient with CHARGE syndrome). The three most frequently occurring pathogenic missense mutations were each found in more than three index patients (p.Ile1028Val, p.Gln1214Arg, and p.Gly2108Arg).…”
Section: Classification Of Chd7 Missense Variantsmentioning
confidence: 99%
“…Four benign variants (p.Ser103Thr, p.Met340Val, p.Gly522Val, and p.Phe2750Leu) were found in more than 15 index persons. Two of these variants (p.Ser103Thr and p.Gly522Val) were found in homozygous states and are, therefore, surely benign (mice with homozygous CHD7 mutations die in early embryogenesis [Bosman et al, 2005] and homozygous CHD7 mutations have never been found in a patient with CHARGE syndrome). The three most frequently occurring pathogenic missense mutations were each found in more than three index patients (p.Ile1028Val, p.Gln1214Arg, and p.Gly2108Arg).…”
Section: Classification Of Chd7 Missense Variantsmentioning
confidence: 99%
“…Somatic mosaicism was detected in the unaffected mother of a sib pair, supporting the existence of germline mosaicism. 45 With the ENU mutagenesis program, Bosman et al 77 reported the identification of mutations in the Chd7 gene in nine of these mice mutant , including six nonsense and three splice-site mutations. These Wheels heterozygous mutant mice revealed a range of defects with reduced penetrance, such as truncations of the lateral semicircular canal, cleft palate, choanal atresia, septal defects of the heart, hemorrhages, prenatal death, vulva and clitoral defects and keratoconjunctivitis sicca that mimics human CHARGE syndrome.…”
Section: Prenatal Diagnosis and Fetal Pathologymentioning
confidence: 99%
“…CHD7 protein is mainly expressed in epithelial cells, olfactory epithelium, and eye, ear, and kidney tissues as well as the vascular system. 26 During the early embryonic stage, CHD7 protein is preferentially expressed in the undifferentiated neuroepithelium and mesenchyme of neural crest origin. 27 These facts closely correspond with the clinical manifestations of CHARGE syndrome.…”
Section: (ϫ35)mentioning
confidence: 99%